Molecular Oligothiophene–Fullerene Dyad Reaching Over 5% Efficiency in Single-Material Organic Solar Cells - Aubele, Anna; He, Yakun; Kraus, Teresa; Li, Ning; Mena-Osteritz, Elena; Weitz, Paul; Heumüller, Thomas; Zhang, Kaicheng; Brabec, Christoph; Bäuerle, Peter (Advanced Materials, 2021)
A novel donor–acceptor dyad, 4, in which the conjugated oligothiophene donor is covalently connected to fullerene PC71BM by a flexible alkyl ester linker, is synthesized and applied as photoactive layer in solution-processed single-material organic solar cells (SMOSCs). Excellent photovoltaic performance, including a high short-circuit current density (JSC) of 13.56 mA cm−2, is achieved, leading to a power conversion efficiency of 5.34% in an inverted cell architecture, which is substantially increased compared to other molecular single materials. Furthermore, dyad 4-based SMOSCs display excellent stability maintaining 96% of the initial performance after 750 h (one month) of continuous illumination and operation under simulated AM 1.5G irradiation. These results will strengthen the rational molecular design to further develop SMOSCs for potential industrial application.
CRIS-Team Scopus Importer:2021-09-10
Keywords: charge transport; device performance; donor–acceptor dyads; long-term stability; single-material organic solar cells